Focused transthoracic echocardiography during critical care medicine training: curriculum implementation and evaluation of proficiency - Beraud, Anne-Sophie; Rizk, Norman W; Pearl, Ronald G; Liang, David H; Patterson, Andrew J (Critical care medicine, 2013)
We designed and implemented a focused transthoracic echocardiography curriculum for critical care medicine fellows participating in 1- and 2-year training programs. We quantitatively evaluated their proficiency in focused transthoracic echocardiography. Prospective study evaluating curriculum implementation and objective assessment of focused transthoracic echocardiography proficiency. Medical and surgical ICUs at an academic teaching hospital. Simulation laboratory. Eighteen critical care medicine fellows. Training in focused transthoracic echocardiography followed by proficiency testing. We assessed the ability of critical care medicine fellows to obtain and interpret focused transthoracic echocardiography images from critically ill patients and a from transthoracic echocardiography simulator. Using a cognitive examination test, we also evaluated each fellow's knowledge with regard to focused transthoracic echocardiography and each fellow's ability to interpret prerecorded focused transthoracic echocardiography images. After training, critical care medicine fellows were able to rapidly obtain five essential focused transthoracic echocardiography views: parasternal long axis, parasternal short axis, apical four chamber, subcostal four chamber, and subcostal inferior vena cava. Fellows were also able to expeditiously identify four important abnormalities: asystole, left ventricular dysfunction, right ventricular dilation and dysfunction, and a large pericardial effusion. A focused transthoracic echocardiography curriculum that includes quantitative measures of proficiency can be integrated into critical care medicine fellowship training programs.